BAKHTIN CIRCLE AND LEONTIEF PSYCHOLOGY: CONTRIBUTIONS TO AN INTERPRETATION OF THE DISCOURSE GENRES CONCEPT - Palomino, Rafael Henrique (Laboratório Editorial FCL-UNESP, 2011)
This paper dedicates itself to approach concepts proposed by the Bakhtin Circle (in his language philosophy) and by Leontief (in his psychology studies), intending to make some considerations about the concept of the discourse genres. The relation between these thinkers’ ideas remarks, especially, problems related to the subjectivity comprehension (in its tension with the social coercions operated upon the language use), to the discourse genres historicity, to the places of materialism and dialectic in genre analysis, and to the concept of refraction, that can be better understood in relation with Leontief’s contributions. Obviously, those are too many questions. Therefore, the present article is limited to some considerations about such themes.